Pengaruh Lokasi Dan Persepsi Harga Terhadap Loyalitas Konsumen Pada Kedai Suhendar Coffe Kota Bima - Nurfalawati Nurfalawati; Herry Nurdin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
This study aims to determine the effect of location on consumer loyalty at Kedai Suhendar Coffee Kota Bima, to determine the effect of price on consumer loyalty at Kedai Suhendar Coffee Kota Bima, to determine the effect of location and price on consumer loyalty at Kedai Suhendar Coffee Kota Bima. The type of research used is associative research, the population in this study is the population used, namely all consumers who visit the unknown coffee shop of the calendar (Unknown Population). Therefore, according to Riduan (2015: 65), to determine the number of samples in an unknown population, the Cochran formula was used and a sample of 96 people was obtained. Data collection techniques in this study are observation, questionnaire sharing in the form of questionnaires and literature study to find the latest and related references related to the title of this article, data analysis used is validity, reliability, classical assumptions, multiple linear regression, correlation coefficient test and determination, partial test and simultaneous test, the results in this study indicate that there is an influence of Location and Price Perception on Consumer Loyalty at Kedai Suhendar Coffe, Bima City.